The effect of short columns on the performance of existing buildings - Kocak, Ali (TECHNO-PRESS, 2013)
In this study, the seismic performance of a residential building which was damaged in the 1992 Erzincan (Turkey) Earthquake (Ms = 6.8) is performed. Damages on columns due to short columns are estimated analytically implementing the shear hinges and results are compared with the observed damages on the building after the earthquake. In seismic performance evaluation, a deformation based approach is adopted, whereby the structural behavior under external and seismic loads is evaluated. Furthermore, the effects of short columns formed by band windows in basement floors are investigated analytically. The sizes of band windows are parametrically changed in order to understand the effects of short columns on overall building behavior.
Keywords: short columns; seismic performance analysis; pushover analysis; non-linear time history analysis; FAILURE; DAMAGE; Engineering